Very Simple Markov‐Perfect Industry Dynamics: Theory. Issue 2 (31st March 2018) - Abbring, Jaap H.; Campbell, Jeffrey R.; Tilly, Jan; Yang, Nan
Abstract : This paper develops a simple model of firm entry, competition, and exit in oligopolistic markets. It features toughness of competition, sunk entry costs, and market‐level demand and cost shocks, but assumes that firms' expected payoffs are identical when entry and survival decisions are made. We prove that this model has an essentially unique symmetric Markov‐perfect equilibrium, and we provide an algorithm for its computation. Because this algorithm only requires finding the fixed points of a finite sequence of contraction mappings, it is guaranteed to converge quickly.